Gambaran Pengetahuan Kader Jumantik di Puskesmas Depok I Sleman - Adiyulianto, Bonaventura; Hestiningsih, Retno; Martini, Martini; Saraswati, Lintang Dian (Jurnal Riset Kesehatan Masyarakat, 2022)
Abstract: Dengue Hemorrhagic Fever (DHF) is a disease that is a public health problem. An effective dengue control effort is the Eradication of Mosquito Breeding Place which involves the participation of the community. Efforts to increase community participation are by forming Jumantik cadres who are tasked with monitoring and counseling the community to carry out PSN. In carrying out his duties properly Jumantik needs to have good knowledge so that it affects his performance. Good knowledge raises awareness, concern, and motivation so that there is an increase in performance. One way that is often used to increase cadre knowledge is through training. Sleman Regency was an endemic area of DHF, Depok sub-district is included in the area with high DHF cases in Sleman Regency. In addition, Depok sub-district is the area with the highest number of confirmed COVID-19 cases in Sleman district. During the COVID-19 pandemic, Jumantik cadres training could not be carried out as usual because the implementation of health protocols required restrictions on holding meetings. The purpose of this study was to obtain an overview of the knowledge of Jumantik cadres during the COVID-19 pandemic in the working area of the Depok I Health Center, Sleman. This type of research was an observational study with a cross sectional design. The population of this research was Jumantik cadres in the working area of Depok I Health Center Sleman with a sample of 151 respondents. Data were collected using a questionnaire and then analyzed univariately. This study found that most Jumantik cadres during the COVID-19 pandemic had less knowledge (65.6%). It is necessary to increase knowledge about dengue disease and mosquito breeding places. Keyword: Knowledge, Cadre, Jumantik, COVID-19